Limbal Pseudoepitheliomatous Hyperplasia Mimicking Ocular Surface Squamous Neoplasia in Palpebral Vernal Keratoconjunctivitis. (6th June 2013) - Malhotra, Chintan; Jain, Arun K.; Thapa, Bikram
Abstract : Purpose . Pseudoepitheliomatous hyperplasia at the limbus can mimic an ocular surface squamous neoplasia. It is an uncommon manifestation of vernal keratoconjunctivitis and has been reported previously in limbal VKC. It, however, has not been reported as a manifestation in the palpebral form of the disease and needs to be kept in the differential diagnosis of a limbal mass lesion in vernal keratoconjunctivitis. Case Report . We report the case of a 24 year old male patient having palpebral VKC and presenting with a papillomatous limbal mass with focal areas of keratinization mimicking an ocular surface squamous neoplasia. An excision biopsy was performed, and the specimen sent for histopathologywhich revealed features of pseudoepitheliomatous hyperplasia with no evidence of dysplasia or malignant transformation. The subepithelium revealed a dense plasma-rich inflammation. Discussion . We report this relatively uncommon presentation of limbal pseudoepitheliomatous hyperplasia mimicking an ocular surface squamous neoplasia in palpebral vernal keratoconjunctivitis. Wide excision as is required for an ocular surface neoplasia may thus be avoided if this entity is recognized in vernal keratoconjunctivitis.